Improving Light Distribution by Zoom Lens for Electricity Savings in a Plant Factory with Light-Emitting Diodes - Li, Kun; Li, Zhipeng; Yang, Qichang (Frontiers in Plant Science, 2016)
The high energy consumption of a plant factory is the biggest issue in its rapid expansion, especially for lighting electricity, which has been solved to a large extent by light-emitting diodes (LED). However, the remarkable potential for further energy savings remains to be further investigated. In this study, an optical system applied just below the LED was designed. The effects of the system on the growth and photosynthesis of butterhead lettuce (Lactuca sativa var. capitata) were examined, and the performance of the optical improvement in energy savings was evaluated by comparison with the traditional LED illumination mode. The irradiation patterns used were LED with zoom lenses (Z-LED) and conventional non-lenses LED (C-LED). The seedlings in both treatments were exposed to the same light environment over the entire growth period. The improvement saved over half of the light source electricity, while prominently lowering the temperature. Influenced by this, the rate of photosynthesis sharply decreased, causing reductions in plant yield and nitrate content, while having no negative effects on morphological parameters and photosynthetic pigment contents. Nevertheless, the much higher light use efficiency of Z-LEDs makes this system a better approach to illumination in a plant factory with artificial lighting.